Extraction of Natural Dye from Allium Cepa and Azadirachta Indica for Dyeing Cotton Fabric (International Journal of Scientific Research in Science and Technology, 2025)
The main objective of the work was to perform extraction and formulation of natural dye using leave extract of Allium Cepa and Azadirachta indica. These plants have higher therapeutic values and effective antimicrobial activity. Their waste Leaves were collected, washed, sterilized, shade dried, and ground to fine powder using mechanical homogenizer. Phytochemical screening was performed in both Leaf extract to determine presence of different type of bioactive components using different solvents like methanol, ethanol, acetone, butanol. The extract collected after hydroalcoholic solvent extraction were treated using Soxhlet apparatus and the extracted phytochemicals were qualitatively analyzed prior to study of the antibacterial activity. The extract was further used to determine the antioxidant activities by free radical scavenging activity (DPPH) method. The efficacy of both extracts was evaluated against growth of E. coli, Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumonia using disc susceptibility test. These extracts showed antimicrobial property with large zone of inhibition. This extract with higher antimicrobial activity could be used to formulate natural dyes on commercial scale. The bioactive component as ingredients on combination behave as an effective natural dye.